The subtle divide: a new method for identifying chop marks on long bone diaphyses using fracture morphology - Okaluk, Tiffany; Dallmann, Justin; Cohen, Haim; Shai, Itzick (Frontiers in Environmental Archaeology, 2026)
IntroductionChop marks provide critical evidence for reconstructing butchery practices, yet their identification criteria are underdeveloped and rely heavily on the presence of sharp force trauma. Sharp force trauma does not occur with every chop, and on long bone shafts in particular, chops can resemble blunt force trauma.MethodsThis study addresses this issue through controlled experiments comparing chop and bash impacts on Sus scrofa femoral diaphyses. Using an Instron 9440 Drop Tower System, impacts were delivered with copper, bronze, iron, and steel axes, as well as a rounded steel hammer, under standardized energy and orientation. Fracture pattern analysis including surface modifications, and impact area shape were recorded for each impact.ResultsStatistical analyses, including Fisher's exact tests, hierarchical clustering, and logistic regression, identified straight impact location shape, non-comminuted fractures, and the presence of SFT as the strongest predictors of chopping.DiscussionBy establishing diagnostic criteria that remain visible even in the absence of SFT, this study provides a robust framework for distinguishing chopping from bashing in archaeological and forensic assemblages, improving our ability to reconstruct tool use, carcass processing, and human behavior from fragmented bone.